Система адаптивной обработки экспертных суждений - Жиляков, Е. Г.; Путивцева, Н. П. (НТУ "ХПИ", 2004)
Запропоновано варіаційний метод обробки результатів парних якісних порівнянь досліджуємих об’єктів з метою визначення їх відносної важливості у вигляді додатних ваг без апріорної розробки шкал суджень. Основою методу є використання інтерпретації елементів матриць парних порівнянь у вигляді функції ваг, що шукаються.

The variational method of handling of results of pairwise qualitative comparisons of investigated objects for the reason of determination of their relative importance as positive weights without elaboration apriori of scales of judgements is offered. In the basis of this method the interpretation of elements of matrixes of pairwise comparisons as functions of required weights is used. The Decision Support System, which will realize choice of best alternative from number available on AHP and on developped variational method, is developing.
Keywords: СППР; нейронные сети; метод анализа иерархий; БД; эксперты